2016
DOI: 10.1038/pr.2016.29
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine responses in primary and secondary respiratory syncytial virus infections

Abstract: Background: Primary respiratory syncytial virus (RSV) infections are characterized by high levels of IL-8 and an intense neutrophilia. Little is known about the cytokine responses in secondary infections. Preschool children experiencing RSV secondary infections were recruited from the siblings of infants admitted to hospital with RSV acute bronchiolitis. Methods: Fifty-one infants with acute bronchiolitis (39 RSV positive, 12 RSV negative) and 20 age-matched control infants were recruited. In addition, seven o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
(45 reference statements)
1
12
0
Order By: Relevance
“…Neutrophil products including myeloperoxidase and neutrophil elastase make significant contributions to mucosal inflammation, increasing airway secretion, coughing, and sneezing (4). Therefore, neutrophils may be critically involved in symptom causation; they also likely contribute to viral transmission by increasing mucus levels, thus enhancing the production of infected respiratory droplets (19).…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil products including myeloperoxidase and neutrophil elastase make significant contributions to mucosal inflammation, increasing airway secretion, coughing, and sneezing (4). Therefore, neutrophils may be critically involved in symptom causation; they also likely contribute to viral transmission by increasing mucus levels, thus enhancing the production of infected respiratory droplets (19).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in humans suggest that RSV can modulate IL-21 secretion. In a cohort study that characterized the primary and secondary cytokine response to RSV infection, IL-21 was not detected in swab nasal secretion samples from infants recruited during two consecutive winters (45). Our data indicated that treatment with IL-21 successfully enhanced humoral responses to RSV, leading to increases in B cell follicles, anti-F (fusion RSV protein) IgG titers, antibody avidity and neutralization capacity.…”
Section: Discussionmentioning
confidence: 74%
“…This response was characterized by further increased release of multiple proinflammatory cytokines and chemokines into both epithelial cell supernatant and mouse BAL. The antiviral response to RSV infection has been associated with increases of various cytokines and chemokines ( 43 , 105 , 123 ), some of which have been shown to be associated with more severe disease. For instance, GM-CSF levels are higher in infants with RSV infection requiring ventilation ( 24 ), and the level of CCL-3 (MIP-1α) has a positive correlation with the duration of required supplemental oxygen ( 33 ).…”
Section: Discussionmentioning
confidence: 99%